The role of granzyme B and other granule proteases as modulators of cytokine activity - Alfonina, Inna (Trinity College (Dublin, Ireland). Department of Genetics, 2012)
Excerpt from introduction: In all vertebrate organisms a properly functioning immune system is absolutely required for protection against infectious agents and also acts as a safeguard against tumour development. Over time we have developed a highly elaborate multifunctional immune system, where a variety of specialised cells recognise danger and respond adequately. How does the immune system eliminate danger? In response to pathogen recognition, immune cells secrete a range of different weapons: cytokines, antimicrobial peptides, cell death-inducing molecules, reactive oxygen species, and proteases, all of which contribute to the eradication of danger (Delves et al., 2011). Of particular interest to this work are proteases; enzymes that cut proteins by catalysing hydrolysis of peptide bonds between amino acids. The family of serine proteases, characterised by a serine residue at their active sites, is the largest family of proteases. These enzymes prominently feature in the arsenal of immune cells and are capable of inducing cell death, regulating inflammation and inhibiting viral replication (Heutinck et al., 2010).
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin